2020
DOI: 10.1038/s41586-020-2338-1
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning of the global epicentre of non-optimal cholesterol

Abstract: Repositioning of the global epicentre of non-optimal cholesterol NCD Risk Factor Collaboration (NCD-RisC)* High blood cholesterol is typically considered a feature of wealthy western countries 1,2. However, dietary and behavioural determinants of blood cholesterol are changing rapidly throughout the world 3 and countries are using lipid-lowering medications at varying rates. These changes can have distinct effects on the levels of high-density lipoprotein (HDL) cholesterol and non-HDL cholesterol, which have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(98 citation statements)
references
References 73 publications
6
86
2
4
Order By: Relevance
“…The mean level of LDL-c found in our study was similar to the mean level of non-HDL-c reported in a recent analysis of 1,127 patients in a pooled population-based study (3.3 mmol/l). [ 18 ] Our results therefore are not in favor of a French specificity in terms of lipids (basis of the “French paradox”). Although the role of cholesterol serum levels as potential risk factor for ischemic stroke has been reported as conflicting, with complex relations, [ 19 – 21 ] cholesterol is undoubtly a major cardiometabolic risk factor [ 22 ]…”
Section: Discussioncontrasting
confidence: 48%
“…The mean level of LDL-c found in our study was similar to the mean level of non-HDL-c reported in a recent analysis of 1,127 patients in a pooled population-based study (3.3 mmol/l). [ 18 ] Our results therefore are not in favor of a French specificity in terms of lipids (basis of the “French paradox”). Although the role of cholesterol serum levels as potential risk factor for ischemic stroke has been reported as conflicting, with complex relations, [ 19 – 21 ] cholesterol is undoubtly a major cardiometabolic risk factor [ 22 ]…”
Section: Discussioncontrasting
confidence: 48%
“…However, many Japanese recognize that egg consumption results in elevation of blood cholesterol level and causes CHD. Moreover, a recent epidemiologic study indicates that blood cholesterol levels are increasing in East Asian countries, including Japan, in contrast to a lowering trend in Western countries [15].…”
Section: Introductionmentioning
confidence: 99%
“…Country-level estimates for mean total and non-HDL cholesterol were obtained from the NCD Risk Factor Collaboration. The NCD Risk Factor Collaboration used publicly available data from population-based surveys to estimate age-standardized total and non-HDL cholesterol for 200 countries, from 1980 to 2018, using a Bayesian model with the Markov chain Monte Carlo algorithm [6]. Although low-density lipoprotein (LDL) cholesterol is often the primary treatment target in lipid guidelines, both total and non-HDL cholesterol (the total mass of cholesterol in atherogenic lipoproteins) has been more widely measured [6].…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…Several developing regions now face a greater burden from elevated cholesterol levels, yet they have lower consumption of lipid-modifying agents as compared to high-income regions [6,7]. Since 1980, parts of Africa and East and Southeast Asia have experienced increases in total and non-high-density lipoprotein (non-HDL) cholesterol, while high-income Western countries have experienced decreases [6]. It is unknown whether recent consumption trends of lipid-modifying agents correspond to the observed changes in cholesterol levels.…”
Section: Introductionmentioning
confidence: 99%